The 1965–1966 Violence, Religious Conversions and the Changing Relationship Between the Left and Indonesia’s Churches - Hearman, Vannessa (Palgrave Macmillan, Cham, 2018)
This chapter discusses the Christian churches’ responses to the 1965–1966 anti-Communist repression in East Java and the conversion of leftist political detainees to Christian religions. Despite tensions in the relationship between the Left and Christian organizations before the repression, the decision to convert by such detainees prompted considerable commentary within church circles in the mid to late 1960s. Drawing on interviews with former detainees, religious cleric and laypersons, Hearman explores the meanings and value that former detainees ascribed to Christian worship, and the relationships they built with clerics over the course of detention and after their release. In so doing, it argues that religious conversion was not solely motivated by the desire to comply with the government requirement to possess a religion.